Students with disability perspectives towards inclusive education at the College of Basic Education in Kuwait: Barriers and challenges - AL Anzi, Naof salem; Alqallaf, Bader Jassim; Alsahou, Hamed Jassim (Journal of Educational and Psychological Sciences, 2021)
This research is a qualitative interpretive case study focuses on the perspectives of (6) students with physical and visual disability who study at college of basic education in Kuwait. It sought to elicit the “voice” of students with disabilities, seeking to identify their experiences of inclusive practice and any barriers to participation. The researchers conducted semi structured interviews. It was processed and analysed through data coding, categorising and emergence of themes. Participants of the current study showed a willingness towards the concept of inclusion with some concerns, which include the cultural, structural, and social barriers of implementing inclusive education. The results of this study emphasise the importance of increasing the knowledge of inclusion and how to deal with students with disability. Overall, recommendations include a need for training courses for the faculty members at the College of Basic Education in the field of disability and inclusion.